"Latinos Have a Stronger Attachment to the Family": Latinx Fathers' Acceptance of Their Sexual Minority Children. Issue 2 (2nd March 2020) - Abreu, Roberto L.; Gonzalez, Kirsten A.; Rosario, Cristalís Capielo; Pulice-Farrow, Lex; Rodríguez, Melanie M. Domenech
Abstract: Parental acceptance is critical to the well-being of sexual minority youth, yet little research has been conducted with fathers, or with Latinx parents of sexual minorities. Understanding Latinx fathers' cultural context and how it operates to facilitate or challenge acceptance of their sexual minority child could contribute new knowledge regarding Latinx culture, Latinx families, and intersectionality of identities to enrich clinical work and future research. This manuscript reports on a phenomenological study of a United States (U.S.) sample of Latinx fathers with a gay and/or lesbian child. Qualitative analysis yielded five main themes: (a) cultural values facilitating acceptance, (b) cultural values interfering with acceptance, (c) specific behaviors facilitating acceptance, (d) validation of intersectionality, and (e) benefits of acceptance. Fathers were involved in the lives of their sexual minority children and placed a priority on their membership in the family above cultural prescriptions of sexual identity, yet were open about the struggle inherent in their children's sexual identity. Fathers' love, investment, and struggle paid off in the form of strong bonds. Findings provide important context to promote practitioners' cultural competence, provide potential implications for cultural adaptations, and suggest areas for future research exploring the intersectionality of ethnicity and sexual identity.